A psychometric investigation of Brazilian Portuguese versions of the Caregiver Eating Messages Scale and Intuitive Eating Scale-2 - da Silva, Wanderson Roberto [UNESP] (2018)
The Caregiver Eating Messages Scale (CEMS) was developed to assess perceived restrictive or critical caregiver messages in relation to food intake and pressure to eat, whereas the Intuitive Eating Scale-2 (IES-2) measures one’s tendency to follow internal cues of hunger and satiety when making eating-related decisions. Both scales are useful in the arsenal of eating behaviour scholars. Here, we developed Brazilian Portuguese translations of both scales and assessed their psychometric properties in Brazilian adults. A total of 288 participants (men = 52.8%) completed the CEMS, IES-2, Body Appreciation Scale (BAS), and a demographic questionnaire. The results of confirmatory factor analysis indicated that the factor structure of both scales had adequate fit following the elimination of items and addition of covariances. Evidence of adequate factorial, convergent and discriminant validity, as well as reliability was identified. Furthermore, correlations of CEMS and IES-2 with BAS scores and body mass index were obtained. Both instruments’ models were found to be invariant across sex, with men having significantly higher scores on three subscales of the IES-2 only. These results provide evidence for the psychometric properties of the CEMS and IES-2 in Brazilian Portuguese-speaking adults. Level of Evidence: V, cross-sectional descriptive study.